Different microbial responses in top‐ and sub‐soils to elevated temperature and substrate addition in a semiarid grassland on the Loess Plateau. (24th April 2019) - Bai, Tongshuo; Tao, Jinjin; Li, Zhen; Shu, Meng; Yan, Xuebin; Wang, Peng; Ye, Chenglong; Guo, Hui; Wang, Yi; Hu, Shuijin
Abstract : The Loess Plateau soil in northwest China originated from wind sediments and is characterized by deep soil profiles and large organic carbon (C) content. Severe soil erosion constantly exposes deep soils to the surface, making the organic C vulnerable to microbial decomposition. Few, however, have so far examined how soil microbial activity and community composition in the deep loess soil respond to perturbations. We examined microbial responses in three layers of a clay‐loam loess (topsoil, 0–20 cm; midsoil, 40–60 cm; subsoil, 80–100 cm) to substrate additions (0.8 g glucose‐C kg −1 soil) under two temperature regimes (25 and 35°C). Soil C:N ratio was significantly larger in the subsoil (20.3) than topsoil (7.4). Glucose addition significantly increased CO2 efflux during a 30‐day incubation period and the relative magnitude of the increase was four times larger in the subsoil than topsoil. The temperature sensitivity ( Q 10 ) of soil CO2 efflux increased significantly with soil depth in the absence of glucose addition (i.e., ambient soil), but it decreased under glucose addition. Also, glucose addition significantly increased phenol oxidase and peroxidase activities in the subsoil, which might contribute to the stimulation of microbial CO2 efflux. Composition of the microbial community was more affected by temperature increase in the topsoil, but more responsive to labile C addition in the subsoil. Together, these results indicated that the composition of soil communities and microbial activities in the topsoil and deep soil responded differently to warming and labile C input. Our findings suggest that organic C in deep loess soils can be highly sensitive to environmental changes, emphasizing the need for more long‐term monitoring and quantitative assessment of organic C release from this important C pool. Highlights: Microbial responses to labile C and warming were examined along a Loess Plateau soil profile. Microbial respiration was more responsive to C addition and warming in deep soil than topsoil. Microbial composition and activity were sensitive to temperature in the topsoil but to labile C in the subsoil. Climate change may facilitate CO2 efflux from deep Loess Plateau soils.